Chinese Character Processing in Visual Masking - Chen, Juan; Zhang, Ye (Frontiers in Psychology, 2022)
It has not been clarified the visual masking function on word processing. The present study systematically compared the effects of three forms of masks (four dots, metacontrast and random patterns) on word identification in three temporal maskings (forward, backward, and sandwiched) paradigms under perceptual and lexical decision tasks separately. Stimuli were varied with word-likeness from random arrangements of strokes up to real words (nonword, pseudoword, and real word). Our findings showed that masking effects were varied with mask form and word likeness under each temporal sequence; the effectiveness of the masking was modulated by the task at hand. These suggested that bottom-up inhibitory may interact with top-down influence contribute to the processing of masked words. Extraction of lexical representation can enhance the perceptibility of meaningful words in the context of low visibility.